PRIVATE CAPITAL FORMATION, PUBLIC SECTOR CAPITAL FORMATION AND ECONOMIC GROWTH IN SOUTH AFRICA - Ahmed Oluwatobi ADEKUNLE (Gusau Journal of Accounting and Finance)
This study examines the relationship between private capital formation, public sector capital formation and economic growth in South Africa. Annual data is used and sourced from WDI to evaluate the study, which spans from 1986-2021. The ARDL approach is employed to analyze the data. The unit root tests indicate that the data are stationary and the bounds test signify that the variables are cointegrated at the long-run. Furthermore, the findings revealed A rise in private capital formation will result in a notable increase in economic growth, as indicated by the coefficients of all the variables in the ARDL long-run result. Private capital formation positively and significantly influenced the nation’s economic expansion. The study recommends increasing private sector capital formation for resilience and offering incentives that encourage adaptation investments, the government should concentrate on creating an environment that allows the private sector to flourish.